2015
DOI: 10.1515/ijamh-2014-0080
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and negative emotions in adolescent girls

Abstract: The main finding was that hopelessness in adolescent girls was associated with endothelial dysfunction. This may indicate that when present, hopelessness places a girl at risk for later cardiovascular disease, whether she has a psychiatric disorder or not. Possible mechanisms for this finding are examined and the surprising finding that conduct disorder is associated with better endothelial function is also discussed. Suggestions for future research are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The innovative features of the current study is on the fact that it included CMDs as variable in the analyses, which indicated that individuals presenting positive CMD criterion have significantly increased their likelihood of belonging to the CVD-risk profile. CMDs have been associated with the abuse of substances such as alcohol and tobacco [47,48], as well as with adolescents' socioeconomic conditions [49] and gender issues [50], which predispose them to experience mental suffering and to act as risk factors for NCD [51].…”
Section: Plos Onementioning
confidence: 99%
“…The innovative features of the current study is on the fact that it included CMDs as variable in the analyses, which indicated that individuals presenting positive CMD criterion have significantly increased their likelihood of belonging to the CVD-risk profile. CMDs have been associated with the abuse of substances such as alcohol and tobacco [47,48], as well as with adolescents' socioeconomic conditions [49] and gender issues [50], which predispose them to experience mental suffering and to act as risk factors for NCD [51].…”
Section: Plos Onementioning
confidence: 99%
“…In this respect, there are two aspects of the role of pro-inflammatory mechanisms: the first reveals the causal relationship between depression and inflammation and/or endothelial dysfunction (ED); the second shows the connection between inflammation, ED, and atherosclerosis [5]. ED and/or elevated levels of peripheral markers of inflammation are found in atherosclerosis and cardiovascular events [23]. Patients at high risk of acute coronary syndrome can be identified based on the elevated levels of inflammatory markers [24].…”
Section: Introductionmentioning
confidence: 99%